Music + Memories = Magic : Wisconsin Nursing Home and Community Projects - Idarraga, Joyce; Sontag, Allison; Yang, Ariel; Peanasky, Alissa (My University, 2015)
Music is a relatively low cost and low risk approach to managing the behavioral and psychological symptoms of dementia. Our first project is bringing the national Music and Memories program into 150 nursing homes. Agency staff will be surveyed close to the start of the project, at three months, and at six months to evaluate the impact of this program on staff and overall work environment. The second project is taking the Music and Memories program into the Eau Claire community by bringing the benefit of personalized music to twenty-five persons with dementia living in their homes with a caregiver.
Color poster with text and photographs.
Keywords: Dementia patients; Nursing home residents; Music therapy; Music + Memory Project; Posters